EKSISTENSI TARI PENDET LANANG DALAM PIODALAN DI PURA PUSEH, DUSUN BAJING, DESA TEGAK, KLUNGKUNG - Suryawan, I Gde; Aprilia, Ni Nengah; Yanti, Ni Luh Gede Mega (Sphatika: Jurnal Teologi, 2024)
The Pendet Lanang dance in Bajing Hamlet, Klungkung is a guardian dance or sacred dance which is part of religious ceremonies, especially in the piodalan at the Puseh temple in Bajing Hamlet, Klungkung which is held at the rahina Buddha Wage Klawu. The Pendet Lanang dance is danced in groups consisting of five adult men as dancers. The tools used by the dancers are a bowl which contains a pair of canang sari which means to invoke the strength of Ida Sang Hyang Widhi and its manifestations and a pair of incense which is symbolized as the God Agni which means as a witness and intermediary to connect people with Ida Sang Hyang Widhi. The uniqueness of the Pendet Lanang Dance is that this dance is only performed during piodalan at Puseh Temple, the dancers must be adult men who are members of the Puseh temple community in Bajing Hamlet who have gone through a purification process, one of the dancers must be a pinandita lanang from Puseh Temple. The aim of this research is to determine the existence of the Pendet Lanang dance in the piodalan at Puseh Temple, Bajing Hamlet, Tegak Village, Klungkung. This research data collection used unstructured observation techniques, interviews, documentation studies and literature studies. It is known that the Pendet Lanang dance is part of the implementation of Piodalan at Puseh Temple and is symbolic of welcoming the descent of the Gods during the Piodalan and is a form of offering before Ida Sang Hyang Widhi Wasa in the form of sacred performance art.